Two Chloroplastic Viroids Induce the Accumulation of Small RNAs Associated with Posttranscriptional Gene Silencing - Martínez de Alba, A. E. (American Society for Microbiology, 2002)
In plants, posttranscriptional gene silencing (PTGS) has been reported for cytoplasmic RNAs from endogenous nuclear genes, transgenes, viruses, and, recently, for a viroid with nuclear replication and accumulation. However, phenomena of this kind have not been described for mitochondrial or chloroplastic RNAs. Here we show that viroids that replicate and accumulate in the chloroplast are also targets of PTGS and this process may control viroid titer.